Implementasi Kebijakan PMK 172/2023 Tentang Dokumentasi Transfer Pricing dalam Meningkatkan Transparansi Pelaporan Pajak dan Kepatuhan Wajib Pajak di Indonesia - Paor, Hilarius Oswaldo; Hartono, Hartono (Reformasi Administrasi, 2025)
The phenomenon of this research is the realization of economic growth being hindered in terms of tax revenue, one of which is tax evasion through transfer pricing practices. This study analyzes the implementation of transfer pricing documentation regulation in improving transparency and taxpayer compliance in Indonesia. This research method uses a type of qualitative descriptive research. The data source consists of interview results from informants directly involved in transfer pricing documentation. The results of this study indicate (1) the implementation of PMK 172/2023 has successfully improved compliance and the quality of transfer pricing reporting in Indonesia. (2) The response from tax authorities shows a strong commitment to providing in-depth and targeted guidance to taxpayers. (3) Entities as Drivers of the Implementation of PMK 172/2023, there has been a significant increase in the number of transfer pricing reports prepared by taxpayers, and Entities as Barriers to the Implementation of PMK 172/2023 include the complexity of the transfer pricing documentation process that must meet various requirements such as Master File, Local File, and Country-by-Country Report.. The recommendations in this study are to strengthen socialization and guidance, enhance the consistency of supervision, and simplify the process of transfer pricing documentation administration.